2021
DOI: 10.1159/000517850
|View full text |Cite
|
Sign up to set email alerts
|

Attitude Matters! How Attitude towards Bariatric Surgery Influences the Effects of Behavioural Weight Loss Treatment

Abstract: <b><i>Introduction:</i></b> Multidisciplinary obesity services at university hospitals usually treat patients with more complex and severe obesity. In addition, patients with Class 3 obesity, in particular, have different attitudes regarding the choices of therapy. <b><i>Methods:</i></b> This explorative study investigated the effect of patient attitudes towards bariatric surgery on body weight change (primary outcome) and psychological improvement (secondary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 56 publications
(75 reference statements)
2
17
0
Order By: Relevance
“…In terms of psychological well-being, the situation is completely unclear. Despite minor weight loss in patients wishing to undergo bariatric surgery in the abovementioned study by Bauer et al [ 29 ], depressive and anxiety symptoms and quality of life had similar improvement in comparison to the patients not wishing to undergo bariatric surgery. Especially for psychologically unstable patients, such lifestyle interventions could help improve compliance post-bariatric surgery, which is known to be critical, e.g., in patients with depression [ 30 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In terms of psychological well-being, the situation is completely unclear. Despite minor weight loss in patients wishing to undergo bariatric surgery in the abovementioned study by Bauer et al [ 29 ], depressive and anxiety symptoms and quality of life had similar improvement in comparison to the patients not wishing to undergo bariatric surgery. Especially for psychologically unstable patients, such lifestyle interventions could help improve compliance post-bariatric surgery, which is known to be critical, e.g., in patients with depression [ 30 ].…”
Section: Discussionmentioning
confidence: 90%
“…The results indicate that participation in such preoperative lifestyle interventions before bariatric surgery led to minor BWL, which contribute to decreased risk during the procedure. However, these intervention programs may have their limitations since Bauer et al [ 29 ] recently showed that having a positive attitude toward bariatric surgery per se hinders an individual's weight loss in a 6-month, multimodal lifestyle intervention. Personal exhaustion toward conservative weight loss programs and a lack of motivation may be underlying factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence indicated that patients preferring OS versus BWLT differed in sociodemographic characteristics, being more likely to be younger [11,12], men [11], and less educated [12], although evidence is mixed [13,14]. Clinically, patients with versus without a preference for OS had a higher BMI [11,13], more previous WL attempts [11,13,14], showed more severe general psychopathology [11] and lower quality of life (QoL) [12], while evidence on depressive symptoms and eating disorder psychopathology is scarce and conflicting [11][12][13][14]. Notably, these were cross-sectional results, comparing patients preferring OS versus BWLT before intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Timeline, consequences, and emotional representations were reduced, and they felt more personal control. Bauer et al ( 64 ) showed that matching the patient's attitude and the treatment methods lead to better weight loss results. Therefore, the evaluation of illness beliefs, that is, the “patient perspective” could be useful parameters for the individualisation and the success of obesity treatment ( 65 , 66 ).…”
Section: Introductionmentioning
confidence: 99%